The Influence of Artificial Intelligence on the Efficiency of Economic Decision-Making among Generation Z Households in Indonesia - Arai Maharati (IHSA Institute, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed financial decision-making by providing intelligent tools that assist individuals in budgeting, expenditure management, savings, investment planning, and financial forecasting. As digital natives, Generation Z has increasingly adopted AI-powered applications such as intelligent financial assistants, budgeting platforms, and generative AI tools to support everyday economic decisions, making it essential to understand how these technologies influence household financial management. Efficient household economic decision-making is critical for achieving financial stability, improving resource allocation, and enhancing long-term financial well-being, particularly in an increasingly digital economy. This study aims to analyze the influence of Artificial Intelligence utilization on the efficiency of economic decision-making among Generation Z households in Indonesia. A quantitative explanatory research design with a cross-sectional survey was employed, involving 374 Generation Z respondents who actively participated in household financial management. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that Artificial Intelligence utilization has a significant positive effect on household economic decision-making efficiency, while Technology Acceptance partially mediates this relationship and Financial Literacy strengthens its positive impact. The study concludes that AI can substantially improve budgeting accuracy, spending control, savings management, investment decision quality, and financial planning when supported by adequate financial literacy and responsible technology adoption, thereby contributing to more effective household economic management among Generation Z in Indonesia.